Helicopter gearbox periodic strut with geometrical discontinuity for vibration and noise reduction - Fengjiao; Wang; Yang; Lu; Heow; Huiyu (My University, 2019)
A novel periodic strut for helicopter cabin noise reduction is presented in this paper. The strut uses monomaterial with periodical changing geometry in the longitudinal direction. To design the strut, a theoretical model is built based on the lumped-mass method. On this basis, a parametric analysis is carried out. The results showed that if the static stiffness and the weight are constants, the stop band of the strut is mainly determined by the periodic number and the cell stiffness ratio. The strut can be quickly designed through reducing the periodic number and increasing the cell stiffness ratio to obtain a lower stop band. Subsequently, a sample strut is designed. Its translational and rotational transmissibility are simulated. It is found that except for the designed longitudinal direction, the strut has broadband vibration attenuation characteristics in the lateral direction. However, resonances appear in some frequencies due to the small damping, which would cause noise amplification. In spite of this, with the novel periodic struts, nearly 20dB noise attenuation appears in the cabin of the helicopter model between 500-2000 Hz.